ANALYSIS OF VOLTAGE DROP IN LOW VOLTAGE NETWORK DISTRIBUTION SYSTEM IN TANTUI UP SUBSTATION KTATNT013 AMBON - SEFNATH J WATTIMENA (CV KULTURA DIGITAL MEDIA, 2022)
The Low Voltage Network Distribution System to the House Connection is the end of the electrical energy service to consumers. A good service portrait can be seen from the quality of the voltage. The nominal value of the voltage must comply with the standards contained in SPLN 1: 1995, namely +5%; -10%. This research uses quantitative analysis research method. The research stage starts from data collection, calculation, analysis, and solution offering. Substation KTATNT013 Department A whose network end is in Kampung Kolam experienced a measured voltage drop of up to 131V at the end house, which has exceeded the SPLN tolerance limit. As a result, some consumer electrical appliances cannot function properly. To overcome this problem, an improvement solution is offered as well as the calculation of voltage drop before and after. The solution in the form of conductor uprating and network reconfiguration reduced the voltage drop from 96.05V (42.40%) to 27.43V (12.11%), while the transformer insertion solution reduced the voltage drop to 14.26 V (6.29%) on the existing transformer Low Voltage Network and 8.3V (3.77%) on the inserted transforme